ANALISIS KINERJA KEUANGAN DENGAN METODE ALTMAN Z – SCORE DAN SPRINGATE PADA INDUSTRI OTOMOTIF YANG TERDAFTAR DI BEI - Wulansari, Murwani (Jurnal Manajemen & Bisnis Jayakarta, 2022)
The purpose of this study was to determine whether the financial condition of PT. Astra Otoparts Tbk, PT. Astra International Tbk and PT. Indomobil Sukses Makmur Tbk is in good health or financial difficulties. The method used is Altman Z Score and Springate S Score. The results of this study indicate that PT. Indomobil Sukses Makmur Tbk is in financial distress using the Altman Z Score and Springate S Score methods.